2009
DOI: 10.1097/mcg.0b013e31818dd94c
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes With Pegylated Interferon and Ribavirin for Male Prisoners With Chronic Hepatitis C

Abstract: Goals-To report our experience with pegylated interferon and ribavirin treatment of hepatitis C virus (HCV) RNA-positive inmates at the Rhode Island Department of Corrections.Background-An estimated 1 out of 3 HCV-infected individuals will spend time in a jail or prison within a 1-year period, making prisons a unique setting for management of chronic HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 25 publications
1
26
1
3
Order By: Relevance
“…SVR rates in prisoners infected with genotype 1 varied between 18% and 43.1%, while those in prisoners infected with genotype 3 were in the range from 50% to 71.4% (3,24,25,26). In the present study, SVR rates at 6 months post-treatment were 75% for all genotypes.…”
Section: Discussionsupporting
confidence: 51%
“…SVR rates in prisoners infected with genotype 1 varied between 18% and 43.1%, while those in prisoners infected with genotype 3 were in the range from 50% to 71.4% (3,24,25,26). In the present study, SVR rates at 6 months post-treatment were 75% for all genotypes.…”
Section: Discussionsupporting
confidence: 51%
“…Efficacy and safety of HCV treatment has been described among prison inmates in both the Rhode Island and Connecticut Departments of Corrections [34,35]. Treatment with pegylated interferon and ribavirin resulted in overall SVR rates of 43%, and 47% respectively, comparable to that of the general population.…”
Section: Prison Inmatesmentioning
confidence: 85%
“…14 Specific to the RIDOC population, studies have reported HCV prevalence rates from 23 to 27 %. 12,25,40,41 We conducted a cross-sectional survey of all incarcerations at RIDOC as of February 2014 and reviewed the electronic medical records (EMR) for data on screening uptake and clinical characteristics (see Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…We selected the total drug costs of treating all 24,25 To capture hypothetical market pricing of newly available and upcoming therapies, we projected costs given either 25 or 50 % reduction or an increase by 25 or 50 % based on current total medication costs. To further account for incarceration periods, we assessed treating those with a remaining length of stay of at least 3 months, at least 9 and 12 months or more.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation